Parents' voices: 'why and how we advocate'. A meta‐synthesis of parents' experiences of advocating for their child with autism spectrum disorder. (22nd July 2016) - Boshoff, K.; Gibbs, D.; Phillips, R. L.; Wiles, L.; Porter, L.
Abstract: Parenting a child with autism spectrum disorder (ASD) can be stressful, and accessing services can add to this stress. Self‐efficacy, agency and advocacy are important for parents when accessing and using services. To develop insight into parental advocacy, a meta‐synthesis was undertaken to consolidate the literature focussing on parents' experiences of advocating for their child with ASD. A qualitative meta‐synthesis was conducted. Fifteen databases were systematically searched by using key terms related to ASD, children, parents/carers, advocacy and qualitative studies. Twenty‐four studies were identified and appraised using an adapted version of the Critical Appraisal Skills Programme tool. Data were synthesized into themes through the steps of review, meta‐aggregation, integration and interpretation. Two overarching concepts emerged, illustrating both the challenging nature of advocacy and the associated personal and societal benefits. These two concepts are supported by eight themes: a life‐long, all‐encompassing challenge; advocacy as a parental coping strategy; advocacy involving working to create a future; balancing roles and needs; isolation versus support; personal impacts of advocacy; benefits of advocacy; and the barriers to advocacy. The experience of advocacy for parents with a child with ASD is complex and intensive, presenting both personal and societal benefits, as well as challenges for parents. In supporting individuals with ASD and family well‐being, service providers need to have an understanding of the advocating role of parents and ensure that opportunities exist for their voices to be heard during service delivery.